Mission impossible?: A cultural change to support scientific integrity. (2nd July 2021) - Schocker, Frauke; Fehrenbach, Heinz; Schromm, Andra B
Abstract : The Research Center Borstel developed a bottom‐up approach based on communication and team scouts to create a culture that fosters research integrity.